GE_GERICHTE P/11216/2023 vom 15. Februar 2024 - GE Cour de justice (2024)
MANIFESTATION;LIBERTÉ DE MANIFESTATION;CONTRAVENTION;LIBERTÉ DE RÉUNION;LIBERTÉ D'EXPRESSION;EXEMPTION DE PEINE | LMDPu.10; LOJ.129.al4; CP.52